(untitled) (The Research of Medical Science Review, 2025)
High-quality nursing care is essential for positive patient outcomes, safety, and satisfaction. The quality of nursing care in Pakistan is still impacted by structural problems such inadequate staffing, inadequate training, and inequalities in facilities, particularly between private and public hospitals. The purpose of this study was to use patient-centered measures to evaluate the standard of nursing care in Pakistani hospitals. Between January 2024 and December 2024, four popular hospitals of Peshawar—two government and two private—were the focus of a cross-sectional, mixed-method research. 400 patients (100 in each hospital) were questioned using stratified random sampling. Participants who were 18 years of age or older, hospitalised for a period of time exceeding 48 hours, and gave their informed permission were eligible. A standardised Patient Satisfaction with Nursing Care Quality Questionnaire (PSNCQQ) was used to gather data, and semi-structured interviews were used to get qualitative data. SPSS (version 25) was used to analyse the quantitative data, and independent sample t-tests were used to compare the groups; p-values less than 0.05 were deemed statistically significant. The findings demonstrated that, for every metric, patient satisfaction was far greater in private institutions. In private hospitals, communication satisfaction was 4.1±0.7, but in public hospitals, it was 3.2±0.8 (p < 0.001). The private sector also shown considerably higher levels of technical skill (4.3±0.5 vs. 3.8±0.6, p = 0.002), empathy (4.2±0.6 versus 3.5±0.7, p < 0.001), as well as responsiveness (4.0±0.8 compared to 3.0±0.9, p < 0.001). Similar patterns were seen in pain management and respect. Patients between the ages of 31 and 50 along with those having postsecondary education had greater levels of pleasure, which was impacted by age and education. Issues like as "attentive nurses" at private hospitals and "overworked staff" from public ones were brought to light by qualitative themes. The quality of nurse treatment in public and private hospitals varies significantly, according to this study. To improve nursing care throughout Pakistan, patient-centered assessments have to be incorporated into certification and quality improvement processes.